Pengaruh Harga, Kualitas Produk, Citra Merek terhadap Keputusan Pembelian Sabun Mandi Lifebuoy di Yogyakarta - Paluvi, Ajeng; Sudarusman, Eka (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to determine the effect of price, product quality, and brand image on purchasing decisions for body wash Lifebuoy in Yogyakarta. The sampling method uses purposive sampling, with 105 respondens. Data analysis method uses in this research in multiple linear regression analysis method. Based on the results of the t test it’s can be seen that price has a negative and insignificant effect on the purchase decision with a significant level of 0,410, the product quality variable has a positive and significant effect on the purchase decision with a significant level of 0,000, and the brand image variable has a positive and significant effect on the purchase decision with a significant level of 0,002. From the analysis o the coefficient of determination can be explained that price, product quality, and brand has a contribution of 0,748 or 74,8% to the decision to purchase Lifebuoy body wash, while the remaining 25,2% is influenced by other variables not examined in this research.